The Applications of Mixed Metal Oxides to Capture the CO2 and Convert to Syn-Gas - Sajan Babhare; Reshma Raskar; Komal Bobade; Abaji Gaikwad (Bulletin of Chemical Reaction Engineering & Catalysis, 2015)
The applications of different mixed metal oxides were explored for the capture of CO2 and convert of CO2 to syn-gas. The several samples of the mixed metal oxides were prepared by the sol-gel, solid-solid fusion, precipitation, molten salt and template methods in order to investigate the performance of mixed mtal oxides to the CO2 applications. These samples were calcined for the 3 h in air at 900 oC. The mixed metal oxides samples were characterized by acidity/basicity, surface area, XRD pattern, SEM images and to capture CO2. The basicity and surface area of the samples of mixed metal oxides were found to be in the range from 0.7 to 15.7 mmol.g-1 and 2.24 to 138.76 m2.g-1, respectively. The ob-tained results of prepared mixed metal oxides by different method were compared for the purpose of searching the efficient materials. The temperature profiles of the captured CO2 by the samples of mixed metal oxides were obtained in the range 100 to 800 oC. The captured CO2 was found to be in the range from 7.36 to 26.93 wt.%. The conversions of CO2 by methane were explored to syn-gas over the mixed metal oxides including the calcium iron lanthanum mixed metal oxides and (5 wt.%) Pd/Al2O3 at 700 oC with the gas hourly space velocities (GHSV) 6000 ml.h-1.g-1 of methane, 6000 ml.h-1.g-1 of CO2 and 24000 ml.h-1.g-1 of helium. © 2015 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)